Edukasi Peningkatan Pengetahuan terhadap Pemanfaatan Rempah pada Masa Pandemi Covid-19 - Evicenna Naftuchah Riani; Wilis Dwi Pangesti; Ima Syamrotul Muflihah (LPPM Akbid Harapan Ibu Pekalongan, 2022)
Covid-19 attacks the human respiratory system. In many cases, the COVID-19 virus infects mild respiratory tract symptoms, while for severe respiratory infections it can lead to pneumonia. This virus can attack anyone, whether babies, children, teenagers, adults and the elderly and does not know gender. Covid-19 cases in Indonesia are increasing day by day. People who have immunity or poor immunity are one of the causes of being easily exposed to the Covid-19 virus. For this reason, it is necessary to prevent transmission by implementing health protocols. However, it is not enough to implement health protocols, it is necessary to make efforts to maintain health such as exercising, eating nutritious foods, besides being able to use spices that are in the environment to be used as herbal drinks as an effort to increase one's immunity. This service activity focuses on educating the use of spices as an effort to increase public knowledge about the usefulness and kinds of spices that can be processed and consumed as an effort to increase the body's immunity in the community. The method used is lecture, discussion and question and answer. Participants actively participate in discussions and ask questions about things that are not understood. The discussion process discussed matters relating to the use of spices in increasing immunity during the COVID-19 pandemic. There is an increase in knowledge of covid-19 and the use of spices for partners.